Acceptance of online sports marketing among Faculty of Sport Science and Recreation Student in UiTM (Perlis) / Radzliyana Radzuwan, Khor Poy Hua and Lim Khong Chiu - Radzuwan, Radzliyana; Khor, Poy Hua; Lim, Khong Chiu (Universiti Teknologi MARA, Perlis, 2013)
The online marketing has gained prominence among sport event tourists due to its sophisticated features. Even though researchers have examined various factors that influence general consumer use of the Internet, but there are limited research conducted on acceptance of online sports marketing. Thus, a survey was conducted to identify the components of benefits perceived (accessibility, flexibility, interactivity and reliability) and components of challenges experienced (technical challenges and organizational and behavioral challanges) in acceptance of online sports marketing. Using the Sport Website Acceptance Model (SWAM) and Psychological Continuum Model (PCM) as its theoretical framework, this study analyzed the data by applying Multivariate Analysis of Variance (MANOVA) and independent sample ttest to test research hypotheses. A number of 126 respondents among the FSR students of UiTM (Perlis) were involved in this present research. Self-administered questionnaire was distributed equally to 63 male and 63 female students. Research was conducted through implementation of systematic simple random sampling. Findings highlight the advancement on four major points, namely the benefits perceived and also the challenges experienced in acceptance of online marketing, besides the facts that online sports marketing can increase individual‟s behavioral intention toward the sports event tourism, and website communication can create favorable attitudes toward sport event.